Examining the Effects of Teacher Feedback on Student Self-Efficacy in Mathematics - Amanah, Atika (Educia Journal, 2025)
This study examines the effects of teacher feedback on student self-efficacy in mathematics, focusing on the impact of feedback types (corrective, praise, and constructive) and feedback frequency. Using a quantitative approach, data were collected from 300 middle school students across three grade levels (6th, 7th, and 8th). Results showed that constructive feedback had the strongest positive correlation with improvements in self-efficacy (r = 0.70), followed by corrective (r = 0.62) and praise feedback (r = 0.48). Additionally, students who received feedback more frequently demonstrated greater improvements in self-efficacy, with the high-frequency feedback group showing the highest increase (M = 0.92). Grade-level differences were also observed, with 8th-grade students showing the most significant improvements. This study contributes to the literature by demonstrating the differential effects of feedback types and the importance of feedback frequency in enhancing student self-efficacy, especially in mathematics.